Comparison of filter lenses versus non filter lens on stereoacuity in high myopic patients - Nayab Bashir; Muhammad Anwar Awan; Agha Saad; Wajeeha Boota; Aliya Khalid; Akram, Syed Nishat (Medical Journal of South Punjab, 2024)
Objective: To determine whether filter lenses improve stereoacuity in high myopic patients compared to non-filter lens. Methods: It was a comparative cross sectional study. This study was conducted in Asif Eye Clinic, Lahore. The study included 66 high myopic patients (40 males and 26 females) aged 18 to 60 years, with myopia ranging from -6.00D to -10.00D. The TNO test, a well-known tool for testing depth perception using random dot stereograms, was used to determine stereoacuity. Initially, each patient’s baseline stereoacuity was measured without filter lenses. Further assessments were taken out using red, green, blue, and yellow filters to see if there were any differences in stereoacuity. To study the variations and estimate the possible benefits associated with each filter, repeated measures ANOVA and paired t-tests were used for statistical purposes. Results: The results indicated that using blue filters in high myopic patients significantly improved their stereoacuity (p = 0.001). Yellow filters also resulted in a slight improvements, with a a p-value of 0.04. However, when applied red or green filters on them, there were no statistically significant differences in stereoacuity were found compared to the non-filter baseline. Conclusion: The outcomes of this study show that using filter lenses, particularly blue ones, can improve stereoacuity in patients with high myopia. This could possibility result in improved performance of vision for those with high myopia. However, more research is required tto validate the findings with a larger and more wide group of patients.